Analisis Pengukuran Kinerja Perusahaan PT XYZ dengan Menggunakan Metode Balanced Scorecard - Yakobus Teofilus; Anas Lutfi (Universitas Tarumanagara, 2022)
The business environment today in Indonesia is shifting to a whole new level of measuring its performances. Rather than only one financial perspective which causes evaluating the customer's needs, the internal processes, and the human resources separately, the company must have a comprehensive tool to link its vision and missions into strategies that can be implemented and measured. This research aims to analyze and explore the linkage of vision, missions into strategy map, also a measurement of performances at the company using SWOT analysis, TOWS analysis, IE matrix, and Balanced Scorecard analysis. This research presents that balanced scorecard measurement could give benefits by exploring the non-financial perspectives that enable the company to create strategic alignment between strategic objectives that link the company’s vision and missions into strategic outcomes and performance driver so can boost the company’s performance.